Effect of Polymer Mixtures on Physical-Chemical Properties of Sandy Soil and Plant Growth - Yang, Qingwen; Pei, Xiangjun; Fu, Cheng (Frontiers in Ecology and Evolution, 2022)
Serious desertification problems were found in alpine grassland of the Qinghai-Tibet Plateau, China. The rehabilitation progress of degraded grassland is slow under natural conditions that have low rainfall and large evaporation. Organic agent-solidified soil is one of the most important measurements that limit desertification and grassland conservation-restoration. However, the characteristics of vegetation growth and development in solidified soil need to be studied in depth. This research is based on the modified carboxymethyl cellulose (MCMC) of independent development. Based on the sand soil taken from moving sandy land of Zoige, potted plants were tested in the environmental chamber at the laboratory. The physical, chemical, and biological characteristics of root soil were monitored for more than 7 months. As a result, the plant biomass in the experimental group increased, lodging rate decreased, drought tolerance and survival rate increased, and the number of plant roots and root surface area index, root cross-sectional area ratio, and root volume ratio increased compared with the matched group. It is shown that MCMC can effectively promote plant root development and improve plant drought tolerance and lodging resistance. We also found that, compared with the matched group, the values of the rhizosphere soil mass, root soil mass, and soil crust layer thickness of the experimental group were much higher, meaning that MCMC has strengthened the root soil-fixation ability and soil-crusting ability of plants. The soil nutrient indexes and bioactivity of the experimental group were higher than the matched group, indicating that MCMC has a positive influence on soil maturation. The quantitative description model of soil aging enhancement of MCMC material during root growth and development was established to explore the soil-fixation mechanism of MCMC plant root succession and provided an important scientific basis and technical support for the conservation and restoration of alpine grassland desertification grassland.